El mar - MacQuitty, Miranda; Greenaway, Frank (Photographer) (Londres ; Nueva York : DK Pub., 2005)
Text and illustrations present such ocean creatures as the manta ray, dolphin, and octopus, explaining their physical structures and how they work.
Includes index.
Text in Spanish.
Keywords: Ocean -- Juvenile literature; Marine animals -- Juvenile literature; Oceano -- Literatura juvenil; Mamiferos marinos -- Literatura juvenil